2016
DOI: 10.1117/1.jbo.21.1.015013
|View full text |Cite
|
Sign up to set email alerts
|

Temperature dependence of nanosecond laser pulse thresholds of melanosome and microsphere microcavitation

Abstract: Abstract. Melanosome microcavitation is the threshold-level retinal pigment epithelium (RPE) damage mechanism for nanosecond (ns) pulse exposures in the visible and near-infrared (NIR). Thresholds for microcavitation of isolated bovine RPE melanosomes were determined as a function of temperature (20 to 85°C) using single ns laser pulses at 532 and 1064 nm. Melanosomes were irradiated using a 1064-nm Q-switched Nd:YAG (doubled for 532-nm irradiation). For comparison to melanosome data, a similar temperature (20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…Threshold fluences of short laser pulses with various widths have been investigated for selective melanosome response [ 10 , 11 , 12 , 13 , 14 , 15 , 16 ], and the threshold fluences of femtosecond‐to‐microsecond laser pulses for melanosome disruption in laser skin treatment have been reported [ 10 , 11 ]. Such studies visually observed the disruption through the grossly apparent immediate whitening response of the skin surface from increased optical scattering.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Threshold fluences of short laser pulses with various widths have been investigated for selective melanosome response [ 10 , 11 , 12 , 13 , 14 , 15 , 16 ], and the threshold fluences of femtosecond‐to‐microsecond laser pulses for melanosome disruption in laser skin treatment have been reported [ 10 , 11 ]. Such studies visually observed the disruption through the grossly apparent immediate whitening response of the skin surface from increased optical scattering.…”
Section: Introductionmentioning
confidence: 99%
“…Melanosome disruption from the net threshold fluences was not shown. Experimental analyses of picosecond‐to‐microsecond laser pulses in selective retina treatment have also been conducted using melanosomes isolated from porcine and bovine eyes [ 12 , 13 , 14 , 15 , 16 ]. However, these analyses investigated the threshold fluences for the microbubble formation around the melanosomes, overstretching the retinal pigment epithelium (RPE) cell membrane [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Schmidt et al investigated the microcavitation processes of retinal pigment epithelium melanosomes and polystyrene microspheres. [7][8][9] Most of these studies were based upon experimental methods and relied on fast laser imaging to capture the transient dynamics of the vapor bubble(s) under different laser, tissue, and event boundary conditions.…”
Section: Introductionmentioning
confidence: 99%